Placental Abnormalities are Associated With Specific Windows of Embryo Culture in a Mouse Model - Vrooman, Lisa A.; Rhon-Calderon, Eric A.; Suri, Kashviya V.; Dahiya, Asha K.; Lan, Yemin; Schultz, Richard M.; Bartolomei, Marisa S. (Frontiers in Cell and Developmental Biology, 2022)
Assisted Reproductive Technologies (ART) employ gamete/embryo handling and culture in vitro to produce offspring. ART pregnancies have an increased risk of low birth weight, abnormal placentation, pregnancy complications, and imprinting disorders. Embryo culture induces low birth weight, abnormal placental morphology, and lower levels of DNA methylation in placentas in a mouse model of ART. Whether preimplantation embryos at specific stages of development are more susceptible to these perturbations remains unresolved. Accordingly, we performed embryo culture for several discrete periods of preimplantation development and following embryo transfer, assessed fetal and placental outcomes at term. We observed a reduction in fetal:placental ratio associated with two distinct windows of preimplantation embryo development, one prior to the morula stage and the other from the morula to blastocyst stage, whereas placental morphological abnormalities and reduced imprinting control region methylation were only associated with culture prior to the morula stage. Extended culture to the blastocyst stage also induces additional placental DNA methylation changes compared to embryos transferred at the morula stage, and female concepti exhibited a higher loss of DNA methylation than males. By identifying specific developmental windows of susceptibility, this study provides a framework to optimize further culture conditions to minimize risks associated with ART pregnancies.